Design of hydrodynamic cavitation assisted intensified tertiary treatment unit for effective degradation of organic micropollutants in pharmaceutical industrial effluent: a case study with triclosan - Mishra, Birupakshya; Mukherjee, Anupam; Mullick, Aditi; Bhandari, Vinay M.; Moulik, Siddhartha (Journal of Water Process Engineering, 2022)
Increasing occurrence of micropollutants and trace amount of persistent organic contaminants (POC's) in the wastewater streams even after the well-established conventional treatment is a threat to human health, aquatic entities, and constitute a formidable challenge for the ecological security. In this regard, hydrodynamic cavi-tation based advanced oxidation treatment has attracted extensive attention towards removal of such micro scale pollutants from wastewater streams in the present scenario. Hence, the present work demonstrates the design and application of a rotating hydrodynamic cavitation (RHC) reactor with stator-rotor arrangement for effective degradation of organic micropollutants (triclosan being taken as the target pollutant) from tertiary effluents occurring in the pharmaceutical sector. The process performance was evaluated through optimization of geo-metric parameters of the reactor, various operating parameters as well as by studying the sole and synergistic performance of the HC process combined with other AOPs. The maximum degradation of Triclosan (TCS) ach-ieved by RHC alone was found to be 35.2 % and in synergism, with ozone, a maximum of 97.6 % degradation was observed. Further, to ensure the mineralization of the components, total organic carbon (TOC) contents of the samples were measured and the degradation pathway was predicted through LC-MS analysis. The techno-economic feasibility of the process were understood through economic and energetic analysis and technology transfer was done for replicating the same study for a pilot scale reactor.
Keywords: Advanced oxidation process; Hydrodynamic cavitation; Micropollutant; Pharmaceutical effluent; Tertiary treatment

Antiviral and ROS scavenging potential of Carica papaya Linn and Psidium guajava leaves extract against HIV-1 infection - Jadaun, Pratiksha; Shah, Prachibahen; Harshithkumar, R.; Said, Madhukar S.; Bhoite, Shubhangi P.; Bokuri, Sowmya; Ravindran, Selvan; Mishra, Neetu; Mukherjee, Anupam (BMC Complementary Medicine and Therapies, 2023)
Antiretroviral therapy is the only treatment option for HIV-infected patients; however, it has certain drawbacks in terms of developing multiple toxic side effects. Thus, there is a continuous need to explore safe and efficacious anti-retroviral agents. Carica papaya Linn and Psidium guajava are known for their various biological activities. In this study, we characterized the bioactive fractions of methanolic leaves extract from both plants using the High-resolution electrospray ionization mass spectrometry (HR-ESI-MS) technique, followed by the investigation of their potential as anti-HIV-1 and antioxidant agents through in vitro mechanistic assays. The anti-HIV-1 activity was examined in TZM-bl cells through luciferase gene assay against two different clades of HIV-1 strains, whereas the intracellular ROS generation was analyzed by Fluorescence-Activated Cell Sorting. Additionally, the mechanisms of action of these phyto-extracts were determined through the Time-of-addition assay. The characterization of Carica papaya Linn and Psidium guajava leaves extract through HR-ESI-MS fragmentation showed high enrichment of various alkaloids, glycosides, lipids, phenolic compounds, terpenes, and fatty acids like bioactive constituents. Both the phyto-extracts were found to be less toxic and exhibited potent antiviral activity against HIV-1 strains. Furthermore, the phyto-extracts also showed a decreased intracellular ROS in HIV-1 infected cells due to their high antioxidant potential. Overall, our study suggests the anti-HIV-1 potential of Carica papaya Linn and Psidium guajava leaves extract due to the synergistic action of multiple bioactive constituents.
Keywords: anti-HIV-1 activity; Anti-retroviral; Bioactive constituents; Carica papaya Linn; Cytotoxicity; HR-ESI-MS; Psidium guajava; reactive oxygen species

Mitochondrial resilience and antioxidant defence against HIV-1: unveiling the power of Asparagus racemosus extracts and Shatavarin IV - Jadaun, Pratiksha; Harshithkumar, R.; Seniya, Chandrabhan; Gaikwad, Shraddha Y.; Bhoite, Shubhangi P.; Chandane-Tak, Madhuri; Borse, Swapnil; Chavan-Gautam, Preeti; Tillu, Girish; Mukherjee, Anupam (FRONTIERS IN MICROBIOLOGY, 2024)
Keywords: IN-SILICO; INHIBIT HIV-1